A Lithic Attribute Analysis on Blades from the Middle Stone Age Site, Hollow Rock Shelter, Western Cape Province, South Africa. (2nd April 2016) - Högberg, Anders
Abstract : This article presents a lithic attribute analysis of blades from the late Middle Stone Age site, Hollow Rock Shelter (HRS), in the Western Cape Province of South Africa. Blades from the Still Bay (SB) Industry have not been described previously, but this artifact category makes up a considerable part of the site's lithic assemblage. Blades were systematically detached from prepared cores with a well-shaped exterior core surface. Despite this, variation in attributes best defines blades from HRS. The lithic assemblage also holds a large amount of SB points. Points and blades are present in the same excavation units and layers, indicating they are contemporary. Results of this study show the difficulties of using attribute analysis for interpreting technological aspects of blade production. It is concluded that integrated experiments, together with comparative studies between sites, are needed to further understanding of SB blades.